PENGUATAN PEMAHAMAN KONSEP MASYARAKAT ASEAN DI KALANGAN APARATUR KELURAHAN KOTA SURAKARTA - Ignatius Agung Satyawan; Salieg Luki Munestri; Lukman Fahmi Djarwono (LPPM UNS, 2017)
Nowadays, the ASEAN Community supported by three pillars: political-security, economy and social-cultural pillars have come into force since the end of 2015. Entry into force of the ASEAN Community is automatically binding on all government and society in ASEAN, including in Surakarta. Some preliminary studies indicate that there are still many government officials do not understand the concept of the ASEAN Community. Village as well as sub-district officials are most strategic unit because they are dealing directly with the public. Therefore, strengthening the understanding among village and sub-district officials is important so that the concept of ASEAN Community can be clearly understood by the society and they are expected to obtain benefit from the ongoing ASEAN Community.Key words: ASEAN Community, ASEAN Economic Community, local government, small scale enterprise.